Permainan Tradisional Kucing-Tikus dan Engklek Anak Usia Dini Melalui Kegiatan Outdoor: Traditional Cat-Mouse and Engklek Games for Early Childhood through Outdoor Activities - Khadijah; Asrima, Nur asrima; siregar, lonita hasraini (Prodi Pendidikan Islam Anak Usia Dini Sekolah Tinggi Agama Islam Negeri Mandailing Natal- Sumatera Utara, 2022)
Early childhood education or Kindergarten education is the initial education taken by everyone in the beginning of education other than elementary school. Early childhood is a small child who has an age range of 0-8 years in which the stages of development and growth in children occur very rapidly. In this day and age, not a few parents often entrust their children or send their children to kindergarten or early childhood education, apart from children having playmates in this education, they are also given a stimulus that parents may not do to their children. This research was made with the aim of developing games that involve many people or in mutual assistance games, apart from introducing traditional games which are now rarely used, this has other benefits such as: training mutual trust, courage, self-confidence and responsibility. Maybe today's teachers and parents rarely introduce this traditional game, let alone the cat-mouse game or often called the cat-and-mouse game in the Christmas area, Natal district, Christmas Mandailing district and in our opinion this game must be developed and even very necessary because to support the extinction one of Indonesian culture.